Profiling of subgingival plaque biofilm microflora from periodontally healthy subjects and from subjects with periodontitis using quantitative real-time PCR - Abiko, Y; Sato, T; Mayanagi, G; Takahashi, N (Journal of periodontal research, 2010)
Abiko Y, Sato T, Mayanagi G, Takahashi N. Profiling of subgingival plaque biofilm microflora from periodontally healthy subjects and from subjects with periodontitis using quantitative real‐time PCR. J Periodont Res 2010; 45: 389–395. © 2010 John Wiley & Sons A/S Background and Objective:  Qualitative and quantitative changes of the subgingival plaque biofilm microflora in periodontal pockets are thought to be associated with the development and progression of periodontitis. The aims of the present study were to quantify the proportions of nine periodontitis‐associated bacterial species and four Streptococcus species in subgingival plaque, and to evaluate their relationship with periodontitis quantitatively. Material and Methods:  Subgingival plaque samples were obtained from 12 periodontally healthy subjects and from 28 patients with periodontitis. The amounts of total and target bacteria were measured by quantitative real‐time PCR using universal and species‐specific primers, respectively. Results:  The proportion of total obligate anaerobes was found to be higher in subjects with periodontitis than in periodontally healthy subjects (p < 0.05). Among obligate anaerobes, Tannerella forsythia (2.04 ± 5.27%, p < 0.05), Porphyromonas gingivalis (0.54 ± 1.41%) and Eubacterium saphenum (0.30 ± 0.96%) were detected at high proportions in subjects with periodontitis, but not in periodontally healthy subjects. By contrast, the proportion of total streptococci was lower in subjects with periodontitis (p < 0.05). Specifically, the proportion of T. forsythia, P. gingivalis or E. saphenum increased (≥ 2.78%) and the proportion of Streptococcus species decreased to virtually undetectable levels, in subjects with periodontitis. Conclusion:  Obligate anaerobes, including T. forthysia, P. gingivalis and E. saphenum, were identified predominantly in microflora from subjects with periodontitis, whereas Streptococcus species were identified predominantly in microflora from periodontally healthy subjects, suggesting a change in the subgingival environment that resulted in conditions more suitable for the survival of obligate anaerobes. The proportion of these obligate anaerobes in the subgingival plaque of subjects with periodontitis appears to be associated with the status of human periodontitis.